STUDI PENURUNAN NITROGEN AMONIUM LIMBAH TAMBAK UDANG INTENSIF DENGAN MENGGUNAKAN ROUGHING BIOFILTER HORISONTAL - harmin sulistyaning titah (Purifikasi, 2004)
The decrease in nitrogen concentration during the nitrification process of wastewater from the intensive shrimp ponds was observed by using the Horizontal Roughing Biofilter. The Horizontal Roughing Biofilter was run continuously with the low loadings and detention time variation of 1.0 , 1.5, 2.0 and 2.5 days. The waste water was taken from the effluent of shrimp ponds in Sidoarjo. The experiment showed that the average removal of nitrogen concentration was greater than 90%. The nitrification process followed the zero order reaction, and the reaction rate were influenced by the initial concentration of nitrogen and the detention time.